Feeding disadvantaged children during the COVID-19 pandemic. (2nd September 2020) - Defeyter, Margaret Anne; Mann, Emily; Wonders, Pauline; Goodwin, Sabine
Abstract : The coronavirus crisis has shone a light on pre-existing social, economic and health inequalities. This article examines what has been done to support children who rely on free school meals and holiday clubs to access healthy, nutritious food